Butterfly Strategy using European call and put options in Monte Carlo scenarios with volatility driven by a GARCH-M (1, 1) Model [Estrategia Mariposa mediante opciones europeas de compra y venta en escenarios Monte Carlo con volatilidad conducida por un modelo GARCH-M (1,1)] (2016)
7